Survival Strategy Berbasis Komunitas (Peran Social Capital dalam Institusi Soa, Negeri, Pela dan Gandong) - Eko Basuki (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
This article discusses the role of social capital in local values of indigenous peoples in Maluku, which are located on Seram Island, Ambon Island, and Lease Islands. The main theme of this article is to answer the question of how social capital plays a role in local values that cause local values to exist, be preserved, institutionalized, and used as the basis for survival strategies. The discussion of community sentiment is used to understand the creation of social capital embedded in the structure of local values.Â